A STRUCTURAL EQUATION MODELING OF FACTORS INFLUENCING CUSTOMER SERVICE STAFFS’ JOB PERFORMANCE OF A FREIGHT FORWARDER COMPANY - Hwangsuphakitkoson, Jareeyakorn; Khamproh, Thanyarat; Sarowart, Athip (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2023)
The objectives of this research were 1) to study the confirmatory structural equation model of factors influencing the job performance of customer service staff in a freight forwarder company, and 2) to analyze factors that influence the job performance of customer service staff in a freight forwarder company. The samples for this research consisted of 405 people who are working in customer service, obtained through convenience sampling. The instrument was a questionnaire. The statistics used in data analysis were descriptive statistics and structural equation modeling (SEM). In the normality tests, the skewness is between -1.069 to 0.081, or the distribution is left-skewed and the kurtosis ranges from -1.037 to 1.112, in which the data were normally distributed. The results of structural equation modeling revealed that the motivation factor and hygiene factor, with factor loadings of .801 and .563 respectively, had an effect on the job performance of customer service staff in a freight forwarder company (95.8% explained variance). All indexes, which were Chi - square (X2) = 3.796, df = 6, p - value = .704, X2/ df = .633, GFI = .998, AGFI = .983, CFI = 1.000, RMR = .031, standardized RMR = .0078, and RMSEA = .000, passed the criteria. This indicated that the structural equation model of factors influencing the job performance of a freight forwarder company in Thailand was consistent with the empirical data. It was pointed out that job performance is influenced by 1) the motivation factors in aspects of advancement, work itself, and being recognized 2) hygiene factors in terms of working environment, organization, and compensation.